Investigating the Relationship Between TQM Practices and Firm's Performance: A Conceptual Framework for Indian Organizations. (2016) - Anil, Anu P.; K.P., Satish
Abstract: Previous TQM studies have been inconclusive in resolving the validity of the universalistic standard for TQM implementation in the organization. The past TQM literature reported mixed and ambiguous relationship between TQM practices and organization's performance. The purpose of this study is to develop and propose the conceptual framework and research model of TQM implementation in relation to organization performance particularly in Indian context. This paper investigates impacts of TQM practices on multiple performance measures as well as the obstacles confronted by Indian organizations. To examine the link more closely the relationship between individual TQM practices and various performance measures were investigated explicitly. A comprehensive review of literature on TQM and quality performance was carried out to accomplish the objectives of this study . The adoption of such a conceptual model on TQM and organization's performance would help managers, decision makers, and practitioners of TQM in better understanding of the TQM practices and to focus on the identified practices while implementing TQM in their companies. Further, the scope for future study is to test and validate this model by collecting the primary data from Indian organizations by using Structural Equation Modeling (SEM) approach for hypotheses testing and to find out the effect of mediators in between TQM practices and organization performance.